Regularity results for p-Laplacians in pre-fractal domains - Capitanelli Raffaela; Fragapane Salvatore; Vivaldi Maria Agostina (Advances in Nonlinear Analysis, 2018)
We study obstacle problems involving p-Laplace-type operators in non-convex polygons. We establish regularity results in terms of weighted Sobolev spaces. As applications, we obtain estimates for the FEM approximation for obstacle problems in pre-fractal Koch Islands.